English language competency for employment purposes: meeting the needs of the industry - Sarudin, lsarji; Zubairi, Ainol Madziah; Nordin, Mohamad Sahari; Tunku Ahmad, Tunku Badariah (IIUM Press, International Islamic University Malaysia, 2011)
The literature on employable graduates indicates that there is a considerable concern regarding the widening gap between the communication skills in English of job applicants and the English language competency required for employment.This paper presents the findings of a study to investigate the industry's perceptions of the importance of graduates' English language competency for employment purposes, the industry's assessment of graduates' English language competency and the industry's initiatives to enhance the English language competency of employees. Data for the study were gathered from 123 respondents from the Financial Services, Manufacturing and Industrial, and Telecommunications, Technology and Media industry sectors using a triangulation of methods comprising a seminar, semi-structured interviews, and a survey questionnaire.The findings of this study indicate that English is the most importont language for employment and consistently assessed in the industry. The industry was also found to be pro-active in enhancing employees' English language competency through in-house training programmes. The paper concludes that due to the competitiveness and volatility of the market environment, there is an urgent need to adequately prepare graduates with skills associated with the English language competency for the 21st century workplace.